2015
DOI: 10.1016/j.devcel.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

REPTOR and REPTOR-BP Regulate Organismal Metabolism and Transcription Downstream of TORC1

Abstract: TORC1 regulates growth and metabolism, in part, by influencing transcriptional programs. Here, we identify REPTOR and REPTOR-BP as transcription factors downstream of TORC1 that are required for ∼ 90% of the transcriptional induction that occurs upon TORC1 inhibition in Drosophila. Thus, REPTOR and REPTOR-BP are major effectors of the transcriptional stress response induced upon TORC1 inhibition, analogous to the role of FOXO downstream of Akt. We find that, when TORC1 is active, it phosphorylates REPTOR on Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
145
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(156 citation statements)
references
References 54 publications
11
145
0
Order By: Relevance
“…Another novel mTORC1 substrate discovered recently is the phosphatidylinositol-5-phosphate 4-kinase γ (PIP4Kγ) (Mackey et al, 2014). Finally, a major new transcriptional effector of TORC1 signaling was identified this year in Drosophila melanogaster , REPTOR (Tiebe et al, 2015). Much like FOXO, REPTOR is phosphorylated by TORC1 and thus sequestered in the cytoplasm by a 14-3-3 protein.…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%
See 1 more Smart Citation
“…Another novel mTORC1 substrate discovered recently is the phosphatidylinositol-5-phosphate 4-kinase γ (PIP4Kγ) (Mackey et al, 2014). Finally, a major new transcriptional effector of TORC1 signaling was identified this year in Drosophila melanogaster , REPTOR (Tiebe et al, 2015). Much like FOXO, REPTOR is phosphorylated by TORC1 and thus sequestered in the cytoplasm by a 14-3-3 protein.…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%
“…Much like FOXO, REPTOR is phosphorylated by TORC1 and thus sequestered in the cytoplasm by a 14-3-3 protein. Upon TORC1 inhibition, REPTOR is liberated by a phosphatase and translocates to the nucleus, where it binds target genes together with another protein, REPTOR-BP (Tiebe et al, 2015). Mammalian equivalents of REPTOR and REPTOR-BP have not yet been characterized, but Crebrf and Crebl2 are homologous human proteins (Tiebe et al, 2015).…”
Section: Regulation Of Mtorc1 and Mtorc2 By Nutrient And Endocrine Simentioning
confidence: 99%
“…Similarly, although all eumetazoans possess at least two MAF-bZIPs, the emergence of large MAF and small MAF orthology groups did not occur until after the divergence of cnidarians and bilaterians (Appendix 2.3). This study also identified a new bZIP family, called REPTOR after its Drosophila member (Tiebe et al, 2015), which emerged from an unidentified bZIP ancestor along the poriferan-eumetazoan stem. All…”
Section: The Metazoan Bzip Network Is Comprised Of Members Of Differimentioning
confidence: 99%
“…I named this family after its Drosophila orthologue, which has been recently identified as a downstream factor of the TORC1 signalling pathway (Tiebe et al, 2015). The origin of the PAR-L and OASIS-L sub-families, and REPTOR family can be traced back to being present in the last common metazoan and eumetazoan ancestor, respectively.…”
Section: Accrual Of the Animal Bzip Repertoire Over The Course Of Holmentioning
confidence: 99%
See 1 more Smart Citation